Rainy Weather : A 4D BOOK - Lee, Sally , 1943- (North Mankato, Minnesota : PEEBLE, 2019)
"Splash! It is raining. Get under your umbrella and find out how rain forms. Bring augmented reality to your students by downloading the free Capstone 4D app and scanning for access to an online article, video, and discussion questions"
Keywords: Rain and rainfall -- Juvenile literature; Weather -- Juvenile literature